Systematic review with meta‐analysis: thiopurines decrease the risk of colorectal neoplasia in patients with inflammatory bowel disease. Issue 3 (4th December 2017) - Lu, M. J.; Qiu, X. Y.; Mao, X. Q.; Li, X. T.; Zhang, H. J.
Summary: Background: Patients with inflammatory bowel disease (IBD) have a high risk of developing colorectal neoplasia. Aim: To investigate whether thiopurines can decrease the risk of developing colorectal neoplasia in patients with ulcerative colitis (UC) or Crohn's disease (CD). Methods: We conducted a meta‐analysis of 24 observational studies involving 76, 999 participants to evaluate the risks of developing colorectal neoplasia in IBD patients receiving thiopurine treatment. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) for the risks of colorectal neoplasia were calculated using a random‐effects model. Results: The overall pooled estimate revealed a protective effect of thiopurine use on colorectal neoplasia in patients with IBD (OR = 0.63, 95% CI 0.46‐0.86). The effect was significant in UC patients (OR = 0.67, 95% CI 0.45‐0.98), but was not significant in CD patients (OR = 1.06, 95% CI 0.54‐2.09). Thiopurines exposure significantly decreased the risk of colorectal cancer (CRC) (OR = 0.65, 95% CI 0.45‐0.96) and advanced colorectal neoplasia (CRC and/or high‐grade dysplasia) (OR = 0.62, 95% CI 0.44‐0.89), but did not decrease the risk of dysplasia alone (OR = 0.90, 95% CI 0.37‐2.21). Tendencies towards the protective effect of thiopurines were distinct in clinic‐based studies (OR = 0.59, 95% CI 0.42‐0.82) and case‐control studies (OR = 0.40, 95% CI 0.26‐0.62), but not in population‐based studies (OR = 0.95, 95% CI 0.55‐1.62) and cohort studies (OR = 0.98, 95% CI 0.81‐1.18). Interestingly, studies conducted in Europe (OR = 0.48, 95% CI 0.31‐0.77), rather than in North America (OR = 0.91, 95% CI 0.67‐1.24), showed the protective effect of thiopurines. Conclusions: This meta‐analysis revealed an antineoplastic effect of thiopurines on colorectal neoplasia in patients with IBD, particularly amongst patients with UC. Abstract : Linked Content This article is linked to Qiu et al and Laharie and Riviere papers. To view these articles visit https://doi.org/10.1111/apt.14498 and https://doi.org/10.1111/apt.14475 .